Scenes from an empty church [videorecording (DVD)] - Corrigan, Kevin, 1969-; Casella, Max; Carter, Natalie; Ryan, Thomas Jay; Tukel, Onur; Tukel, Onur (Dark Sky Films, 2021)
In a locked-down NYC, two priests reluctantly open their church doors to parishioners seeking salvation, leading to a series of enchanting encounters with some of the city's sweetest, wildest and weirdest.